Religious Aspect of Spiritual Development of the Elder Teenagers - Martišauskienė, Elvyda (Acta Paedagogica Vilnensia, 2000)
Personal relations reveal the personal spirituality as a transcendental potency. In this article the religious aspect of the relations of elder teenagers is discussed in various levels (mental, emotional and behavioural). The positive attitude towards belief in God or Church was characteristic to approx. 3/4 of the teenagers in our research, but only 16,6% of them had already reached the stage of the personal faith. This proportion remains unchanged also if measured in the field of the religious feelings. However, the range of indifferent (18,6%) or actively antireligious (7,2%) attitudes falls down twice if based on the evaluations of own acts. This is a base for hopeful conclusions about the religious aspect of the spiritual development of the teenagers.
Keywords: spirituality; spiritual development; teenagers; religious feelings; belief in God